SWOT Analysis of e-Governance - Karpagavalli, V. (Indian Journal of Computer Science, 2021)
India is the largest democracy in the world, has much to gain from e-Governance, citizen participation is important for good governance. e-Governance needs to transform at all levels of government but the focus should be on local administration since local administration is the closest to citizens. The coherence between people and the local government authorities is determined by several issues like public services, local area development, education etc. Thus, e-Governance primarily in local administration has to be improved. The penetration of internet, telecommunication services in India has increased in the last decade and this gives a ray of hope to citizens of India to fight with long persisting problems of poverty, corruption, regional disparity, and unemployment. However, at the same time due to slow pace of project completion and resistance from government employees and citizens too has not given the desired result. The present exploratory work is an attempt for understanding the effectiveness of e-Governance in local administration with reference to Tirupur district.